Optimization of planting date and irrigation strategy for sustainable cotton production - Fan, Hongjian; Xue, Lu; Ma, Hao (Frontiers in Sustainable Food Systems, 2024)
Optimizing irrigation strategies and adjusting planting dates are crucial for enhancing the sustainability and profitability of cotton production, especially under constrained water resources. This study involved calibrating and validating crop parameters within the AquaCrop model using data from 2017-2018 on soil moisture, cotton growth, biomass, and yield. The model was then used to simulate the biomass and yield of cotton under mulch drip irrigation across various irrigation levels (18 to 54mm in six increments) and planting dates (ranging from March 23 to May 3) over a 30-year period from 1988 to 2017 in the southern Xinjiang oasis. The AquaCrop model demonstrated robust performance in simulating cotton canopy cover, aboveground biomass, and soil moisture across different irrigation and planting scenarios, with normalized root mean square error (NRMSE) below 20% and high correlation coefficients (R2) and synergistic indices (d) close to 1. Despite slight underestimations in evapotranspiration (ET) and yield (Y), the model proved effective for scenario simulation. The findings indicate that while planting date has a minor impact on the stability and sustainability of cotton production, increasing the irrigation quota significantly enhances these attributes. Notably, an irrigation quota of 495mm yielded high water use efficiency without markedly reducing cotton yield. Strategic postponement of planting dates and adoption of early-maturing cotton varieties can further optimize water conservation, offering a strategic approach to adapt to water scarcity and climate change, tailored to regions with varying water endowments.